Three-dimensional geometrical drawing in three cultures - Mitchelmore, Michael C.
This study compares spatial and three-dimensional drawing ability in the United States, England, and Jamaica. It suggests that the observed differences reflect cross-cultural differences in attitude towards the use of spatial models in thinking, as partly revealed by the degree of geometrical emphasis in the schools' mathematics curriculum. Differences in degree of social conformity in the three countries contribute to the variation in gender differences
doi: 10.1007/BF00304356
Keywords: Drawing